Analisis Film “Home Sweet Loan” Terkait Isu Sosial Sandwich Generation menggunakan Teori Semiotika John Fiske - Athella Inaia Dhia Haretri; Dwi Puji Prabowo (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
Film is a communication medium that has the power to convey social messages to audiences through narrative and visuals. One of the social phenomena currently being extensively discussed is the issue of the sandwich generation, which is the first topic in the "Home Sweet Loan" film. With a qualitative approach and John Fiske's semiotic analysis, this research aims to explore how the sandwich generation issue is represented in the "Home Sweet Loan" film with three levels of analysis: reality, representation, and ideology. This study can contribute to providing a deeper understanding of how films can play a role in depicting relevant social issues and influencing society's perceptions of these social phenomena.